Afforestation on Community Land in the Semi-arid Tropics of Gujarat - an Economic Analysis - Pande, V. C.; Nambiar, K. T. N.; Kurothe, R. S.; Singh, H. B. (Indian Forester, 1999)
The existing fodder and fuelwood scenario in Semi-Arid Tropics entails large scale plantation on lands unsuitable for cultivation, including community lands which are open to biotic interferences. This study presents the results of afforestation programme carried out during 1985-86 through 1988-89 in the Navamota Watershed in terms of financial implications of present Forest Department Policy to open the plantation area for community after five years.